2017
DOI: 10.1007/s13577-017-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30e regulates neuroinflammation in MPTP model of Parkinson’s disease by targeting Nlrp3

Abstract: Accumulating evidences suggest that neuroinflammation is a pathological hallmark of Parkinson’s disease (PD), a neurodegenerative disorder characterized by loss of dopaminergic neurons in substantia nigra pars compacta (SNpc). MicroRNAs have been recently recognized as crucial regulators of inflammatory responses. Here, we found significant downregulation of microRNA-30e (miR-30e) in SNpc of MPTP-induced PD mice. Next, we employed miR-30e agomir to upregulate miR-30e expression in MPTP-treated mice. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 29 publications
2
77
0
1
Order By: Relevance
“…Further studies confirmed that miR‐30e directly targets NLRP3, suppresses its expression, and prevents subsequent activation of the NLRP3 inflammasome. It is associated with decreased expression of caspase‐1 and ASC and a reduction in IL‐1β and IL‐18 release …”
Section: Nlrp3 Inflammasome‐mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies confirmed that miR‐30e directly targets NLRP3, suppresses its expression, and prevents subsequent activation of the NLRP3 inflammasome. It is associated with decreased expression of caspase‐1 and ASC and a reduction in IL‐1β and IL‐18 release …”
Section: Nlrp3 Inflammasome‐mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
“…It is associated with decreased expression of caspase-1 and ASC and a reduction in IL-1β and IL-18 release. 136…”
Section: Small-molecule Inhibitors Of the Nlrp3 Inflammasomementioning
confidence: 99%
“…46,47 Besides, several kinds of microRNA (eg, miR-7 and miR-30e), which are increased in PD brains, could directly activate inflammasome in microglia. 46,48 Similar to the situation in AD, inflammasome products released by microglia within substantia nigra trigger the inflammatory cascades in PD brains. Processive inflammasome activation in microglia may be a sustained stimuli of neuroinflammation that drives progressive dopaminergic neuropathology and promotes fibrillar α-synuclein accumulation.…”
Section: Inflammasome Activation In Parkinson's Diseasementioning
confidence: 97%
“…Fibrillar α‐synuclein in microglia leads to impairment of mitochondrial endocytosis and lysosomal dysfunction, which cause ROS dysregulation and activate inflammasome . Besides, several kinds of microRNA (eg, miR‐7 and miR‐30e), which are increased in PD brains, could directly activate inflammasome in microglia . Similar to the situation in AD, inflammasome products released by microglia within substantia nigra trigger the inflammatory cascades in PD brains.…”
Section: Inflammasome Activation In Microglia/macrophage Is the Resulmentioning
confidence: 99%
“…However, miR‐155 knockout mice models transduced with AAV2‐SYN, exhibit a remarkably decreased proinflammatory response, without a loss of dopaminergic neurons . It was recently shown that miR‐30e improves neuronal damage, neuroinflammation and dyskinesia via targeting Nlrp3 expression and inhibiting NLRP3 inflammasome activation in a MPTP‐induced PD mice model . MiR‐30e levels were downregulated after MPTP injection, suggesting miR‐30 might also have a role in the pathogenesis of PD.…”
Section: Mirnas and Long Noncoding Rnas In Diseasementioning
confidence: 99%